“CPR Posture” for Hemorrhage Control (International Journal of First Aid Education)
Bleeding from traumatic injury is a major source of morbidity and mortality, however, little data is available to aid guidelines and curriculum developers in best practice of applying direct pressure when treating or teaching how to stop life-threatening hemorrhage. Hypothesis: This study investigated the use of two-handed pressure with bent arms versus two-handed pressure with straight arms to apply direct pressure to a hemorrhage model. Methods: Participants, recruited as a convenience sample, were randomized and instructed to use either two hands overlapping using arm strength only, or two hands overlapping with arms straight in a “CPR-like” position to apply force to a standardized hemorrhage control trainer with electronic feedback (Z-Medica), set to record a minimum pressure of 3-psi (155 mmHg); representing as satisfactory pressure to occlude blood flow. Participants were allowed to train for 30 seconds and then were asked to hold pressure at or above 3-psi for a three-minute time period. Participants were not given any feedback during testing. The program output reported the percent of time above the 3-psi pressure following participant completion of the three-minute time period. Results: Thirty participants were enrolled and had data available for analysis. Demographics were statistically similar across groups. When using bent arms, participants provided pressure at or above 3-psi 63.7 % (SD 33.1) of the time. Participants using the “CPR posture” were above 3-psi 100% (SD 0) of the time [mean difference 36.27% (95% CI 18.78-53.75%). The difference between the two experimental arms remained statistically significant when examined by age, gender, or medical experience. Conclusions: A straight-armed “CPR posture” allowed participants to successfully apply pressure to stop simulated bleeding, according to study parameters, 100% of the time. This information provides evidence about the most efficient way to provide high quality direct pressure to stop life-threatening hemorrhage. This method appears applicable to a broad demographic. As this posture is already widely taught in CPR classes, it can be readily adopted for teaching or controlling hemorrhage.